Pregunta
upstudy study bank question image url

Sowe for \( x \) and \( y \) simutanously \( 2 x-y=8 \) \( y=x^{2}+4 x-23 \) 12

Ask by Maxwell Gough. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solutions are \( x = -5, y = -18 \) and \( x = 3, y = -2 \).

Solución

Solve the system of equations \( 2x-y=8;y=x^{2}+4x-23 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-y=8\\y=x^{2}+4x-23\end{array}\right.\) - step1: Substitute the value of \(y:\) \(2x-\left(x^{2}+4x-23\right)=8\) - step2: Simplify: \(-2x-x^{2}+23=8\) - step3: Move the expression to the left side: \(-2x-x^{2}+23-8=0\) - step4: Subtract the numbers: \(-2x-x^{2}+15=0\) - step5: Factor the expression: \(\left(-x+3\right)\left(x+5\right)=0\) - step6: Separate into possible cases: \(\begin{align}&-x+3=0\\&x+5=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x=-5\end{align}\) - step8: Calculate: \(x=3\cup x=-5\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=3\\y=x^{2}+4x-23\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=x^{2}+4x-23\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-5,-18\right)\cup \left(x,y\right) = \left(3,-2\right)\) The solutions to the system of equations \(2x-y=8\) and \(y=x^{2}+4x-23\) are \((-5,-18)\) and \((3,-2)\).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve for \( x \) and \( y \) simultaneously using the two equations: 1. From the first equation, \( 2x - y = 8 \), we can express \( y \) in terms of \( x \): \[ y = 2x - 8 \] 2. Substitute \( y = 2x - 8 \) into the second equation \( y = x^2 + 4x - 23 \): \[ 2x - 8 = x^2 + 4x - 23 \] 3. Rearranging gives: \[ 0 = x^2 + 4x - 23 - 2x + 8 \] \[ 0 = x^2 + 2x - 15 \] 4. Now factor the quadratic: \[ (x - 3)(x + 5) = 0 \] Therefore, \( x = 3 \) or \( x = -5 \). 5. Now, substitute these \( x \) values back into \( y = 2x - 8 \): For \( x = 3 \): \[ y = 2(3) - 8 = 6 - 8 = -2 \] For \( x = -5 \): \[ y = 2(-5) - 8 = -10 - 8 = -18 \] Thus, the solutions are: 1. \( (x, y) = (3, -2) \) 2. \( (x, y) = (-5, -18) \) Now you have two points where the equations intersect! Isn't it cool how algebra can connect those dots? Keep diving into the world of equations; it's like a treasure hunt for solutions!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad